Equine Assisted Activities Have Positive Effects on Children with Autism Spectrum Disorder and Family Functioning - Gonca Ozyurt; Kursat Ozcan; Cagla Dinsever Elikucuk; Ugur Odek; Selcuk Akpinar (Montenegrin Sports Academy, 2020)
Equine-assisted activities (EAA) have emerged as a new method of treatment for children diagnosed with autism spectrum disorder (ASD) in recent years. This study aimed to evaluate the effectiveness of EAA in the areas of social functioning, autistic behaviours, family functioning, and clinical severity for children diagnosed with ASD. The participants were 24 children (4-12 years old) diagnosed with ASD and their mothers. Subjects were randomized into two groups, and the programme consisted of eight sessions of EAA. A social communication questionnaire and clinical global impression scale were used to evaluate the severity of autistic behaviours, and family assessment device was used for family functioning, while the Beck Depression Inventory was used to evaluate the severity of maternal depression. The results suggested that the severity of ASD decreases and improvements in maternal mental health and family functioning were observed in the experimental group, while no significant results were observed in the control group. This study provided preliminary evidence that an eight-week EAA can provide significant improvements in terms of both family and child functioning for children diagnosed with ASD. Further studies in larger samples are needed to investigate these effects.